(untitled) (Research, Society and Development, 2024)
The Covid-19 pandemic had major impacts on the quality of life and health status of the world population, highlighting the health professionals who were at the forefront of the population’s care. After the initial infection, a condition characterized by the persistence of symptoms for weeks that can set in is Long Covid. Therefore, the objective of the research using the integrative review methodology is to evaluate the impacts of Long Covid on the quality of life and health status of these professionals. The search was carried out in the databases PubMed, Periódicos Capes and Biblioteca Virtual de Saúde using the descriptors: Post-Acute Covid-19 Syndrome AND quality of life AND health status AND healthcare workers, for articles in English and Portuguese between the years 2020 to 2023. They were analyzed 7 articles and as a result it was observed that none of these addressed the impacts of Long Covid on the quality of life and health status of healthcare professionals. It is concluded that it is necessary to carry out research with this specific audience, given the degree of exposure and infection during the pandemic.